Participation in daily life for adults with profound intellectual (and multiple) disabilities: How high do they climb on Shier's ladder of participation?. (March 2021) - Talman, Lena; Stier, Jonas; Wilder, Jenny; Gustafsson, Christine
Participation is the goal of Swedish disability policy, but it is difficult to achieve for adults with profound intellectual (and multiple) disabilities (PI(M)D). Since these adults are dependent on others in every aspect of their lives, others control their ability to participate in everyday life decisions. This study used observations, analyzed with Shier's ladder of participation, to elucidate and describe participation in daily life for adults with PI(M)D living in a group home. The results showed that the adults often reached the first three levels of Shier's ladder, one adult reached the fourth level once, and no one reached the fifth level. Participation on a higher level, therefore, seems hard to reach for adults. Staff members' attitudes toward the adults' capability can also be a barrier to participation. Applying Shier's ladder of participation can provide valuable information that might lead to increased participation in daily life for adults with PI(M)D.